THU0285 Use of contraceptive methods in a single center cohort of systemic lupus erythematosus from argentina. (15th June 2017) - Gomez, RA; Paniego, FM; Carrasco, M Garcia; Dubinsky, D; Nasswetter, G
Abstract : Background: Systemic Lupus Erythematosus (SLE) may associate with flares, an unfavorable course and the need of teratogenic treatment during pregnancy. Not every contraceptive method (CM) may be used in this patients. There are guidelines for their use according to existing morbidity and SLE activity 1 . Objectives: Describe the use of CM in a cohort of outpatients with SLE Methods: Descriptive, observational, cross-sectional study. Patients ≥16 years old with SLE (SLICC 2012) and ≥1 visit during the last year of our database were included. Those with menopause were excluded. We analyzed demographic data; disease duration; antiphospholipid antibodies (aPL) and antiphospholipid syndrome (APS) (Sapporo 2006); socioeconomic status (Graffar scale); disease activity (SELENA-SLEDAI) and accrual damage (SLICC); use of teratogens: Methotrexate (MTX), Mycophenolate (MYC), Cyclophosphamide (CYC), biologic drugs (BD), self-reported sexual status (active/non active) and CM: intrauterine device (IUD), condom (Cdm) and hormonal contraceptive pill (CP). Results: 132/219 were included. Female 91.6%, age: 30.1 (16–49) years, disease duration: 38.5 (1–324) months, SELENA-SLEDAI: 3.5 (0–29), SLICC: 0.5 (0–5). Sexual status and use of CM: were available for 120 patients. Sexually active (SA) 73%, female 77%. CM in SA patients: 74%: 5% CP, 77% Cdm and 18% IUD. CM in female patients stratified by Graffar (GF): GF I (n=1): none SA; GF II: (n=19): 84% SA, 75% of them used CM (75% Cdm, 25% IUD); GF III (n=33): 82% sexually active, 81% used CM (86% Cdm, 14% IUD), GF IV (n=41) 75% SA, 68% used CM (9% CP, 71% Cdm, 19% IUD), GF V (n=4) 100% SA, 50% used CM (50% CP, 50% Cdm); GF NA (n=11) 55% SA, 83% used CM (80% Cdm, 20% IUD). CM in female patients stratified by SLE activity: SLEDAI <3 (n=62): 76% SA, 77% of them used CM (3% CP, 83% Cdm, 14% IUD); SLEDAI 3–12 (n=42): 81% SA, 76% used CM (8% CP, 69% Cdm, 23% IUD); SLEDAI >12 (n=60): 60% SA, 67% used CM (100% Cdm). CM in female patients using teratogenic drugs: MTX (n=8): 100% SA, 75% of them used CM (17% CP, 66% Cdm, 17% IUD); MYC (n=20): 80% SA, 88% used CM (71% Cdm, 29% IUD); CYC (n=3): 33% SA, 100% used CM (100% Cdm); Belimumab (n=1): 100% SA, 100% surgical CM (tubectomy). aPL was evaluated in 96/132 patients. 17/96 had positive aPL and 5/17 fulfilled APS criteria. 2/17 patients had no CM data available, none with APS. 9/17 patients with aPL were female, 55% SA and all of them used Cdm. 3/5 patients with APS were female, all SA, 66% used Cdm. Conclusions: Condom was the most reported CM. Use of CM was more frequent in the upper social stratus (GF I-III) respect to the lower (GF IV-V). The proportion of sexually active female patients was similar in those using teratogenic drugs compared with who had not used them. The self-reported sexual status was similar despite of SLEDAI stratification, being similar in patients with low or high disease activity. We deem necessary education, counseling and evaluation of use of the CM in every visit of patients with SLE. References: Andreoli L, Bertsias GK, Agmon-Levin N, et al. Ann Rheum Dis, doi:10.1136/annrheumdis-2016–209770. Disclosure of Interest: None declared